2021
DOI: 10.1096/fj.202002674rr
|View full text |Cite
|
Sign up to set email alerts
|

A novel imidazolinone metformin‐methylglyoxal metabolite promotes endothelial cell angiogenesis via the eNOS/HIF‐1α pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Human Proangiogenic Protein Array. ECs at 80% confluence were transfected with Ad-GPR39 or Ad-GFP as control, and the Proteome Profiler Human Angiogenesis Array (R&D Systems, #ARY007) was performed as described previously (58).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Proangiogenic Protein Array. ECs at 80% confluence were transfected with Ad-GPR39 or Ad-GFP as control, and the Proteome Profiler Human Angiogenesis Array (R&D Systems, #ARY007) was performed as described previously (58).…”
Section: Methodsmentioning
confidence: 99%
“…pnas.org saphenous vein were ligated while the animal was under anesthesia (58). Blood flow was measured before, immediately after, and at 1, 7, 11, 14, 21, and 28 d after femoral arterial ligation using laser Doppler imaging and a PeriScan PIM 3 System (Perimed).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin, the first-line drug for type 2 diabetic mellitus, also has a specific regulatory effect on the process of angiogenesis. The research found that intraperitoneal injection of metformin exhibits potential for improving endothelial function and the wound-healing process in mice models without affecting their blood glucose levels 188 . Recent studies have also revealed that another FDA-approved anti-diabetic class of drugs, gliflozins, which lower blood glucose by suppressing kidney glucose reabsorption by inhibiting sodium-glucose cotransporter 2 (SGLT2) 189 , are also potential small molecule drug candidate for treating PAD.…”
Section: Trends In Therapeutic Angiogenesis For Padmentioning
confidence: 99%
“…In addition, endothelial nitric oxide synthase (eNOS) produces nitric oxide to help regulate vascular function and participates in the regulation of EC repair and proliferation 14 . Our previous study suggested that eNOS exerts biological functions downstream of miR-126-5p; however, its expression level is positively correlated with that of miR-126-5p 10 .…”
Section: Introductionmentioning
confidence: 99%